CREATING MANIPULATIVES: IMPROVING STUDENTS' CREATIVITY THROUGH PROJECT-BASED LEARNING - Ummah, Siti Khoiruli; Azmi, Rizal Dian; In’am, Akhsanul (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2019)
The purpose of this study is describing the implementation of project-based learning model and analysing the student’s creativity improvement in the subject of learning media. We describe the implementation of project-based learning based on our note of the learning syntax during one semester. Then, compared the students’ product to measure their creativity improvement in the aspects of originality, novelty, and flexibility. This study used descriptive-qualitative method and involved the students who took the learning media course as its subjects. The results showed that there was an improvement of the students’ creativity in the project-based learning implementation. The improvement was measured in the making of the manipulatives. The students’ flexibility and novelty were good, while their originality was fair.